FORMATION OF SOCIAL LEGAL CONSCIOUSNESS IN THE PROGRESS OF HUMAN CIVILIZATION - Орденов, С. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article examines the social and cultural foundations of the formation of public legal consciousness in the process of human development; are the historical conditions of the law.